RANCANG BANGUN SISTEM INFORMASI MANAJEMEN POSYANDU DI KECAMATAN SEMARANG SELATAN (Information Technology and Telematics, 2013)
Development of posyandu information system (SIP) to improve health services for mothers and children under five in the Southern District of Semarang. This activity is carried out by cadres posyandu by recording and reporting using SIP instrument.  SIP generated information such as posyandu care statements include statements toddler, mother reports, immunization reports, reports of vitamin A and visitor reports.  Development of a prototype system is based on the stages. Based on preliminary research, the resulting information is difficult to access the SIP before re-developed and has not produced the complete, accurate, and clear.  The purpose of this research is to develop posyandu information system to support health services for mothers and children under five web-based.  The system was developed with the PHP programming language and MySQL. Development of SIP can overcome the problems associated with the quality of information and clarity of the information generated SIP. There are several things that a weakness of the system that the system is not able to display graphics update D / S per month (the number of children present at posyandu services divided by the total number of children region posyandu).   Keywords : Information system, Posyandu, SIP.